2019
DOI: 10.1002/asia.201801585
|View full text |Cite
|
Sign up to set email alerts
|

Selective Fluorescence Turn‐On Sensing of Phosphate Anion in Water by Tetraphenylethylene Dimethylformamidine

Abstract: A tetraphenylethylene (TPE) derivative bearing two dimethylformamidine units was synthesized. The dihydrogen chloride salt of this TPE derivative was soluble in water and showed almost no emission. By addition of phosphate anions, the dihydrogen chloride salt could be transformed into the monohydrogen chloride salt, which was barely soluble and emitted strong fluorescence through aggregation‐induced emission (AIE), while many other anions could not bring about a fluorescence enhancement. Meanwhile, the dihydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
(98 reference statements)
1
10
0
Order By: Relevance
“… [13] TPE derivatives have also received significant interest in the development of supramolecular sensors which couple a luminescent response with molecular recognition events. [ 14 , 15 , 16 , 17 , 18 ] However, the considered employment of TPE‐derivatives within supramolecular host systems remains scarce,[ 19 , 20 , 21 , 22 ] with the overwhelming majority of reported examples reliant on irreversible chemical modification of the AIEgen core to sense the guest species. [23] …”
Section: Introductionmentioning
confidence: 99%
“… [13] TPE derivatives have also received significant interest in the development of supramolecular sensors which couple a luminescent response with molecular recognition events. [ 14 , 15 , 16 , 17 , 18 ] However, the considered employment of TPE‐derivatives within supramolecular host systems remains scarce,[ 19 , 20 , 21 , 22 ] with the overwhelming majority of reported examples reliant on irreversible chemical modification of the AIEgen core to sense the guest species. [23] …”
Section: Introductionmentioning
confidence: 99%
“…D2 ligand was found to selectively sense both PO 4 3− and HPO 4 2− anions by forming a complex with an anion-to-ligand ratio of 4:2 (Scheme 8), thereby triggering an enhancement of blue emission (27- and 20-fold, respectively) due to RIR mechanism of TPE, i.e., anion-coordination-induced emission [101]. More recently, Zheng et al reported selective fluorescence turn-on sensing of PO 4 3− in water by TPE-derivative D3 [102]. The emission response is due to the fact that PO 4 3− abstracts a proton from D3.2HCl to form D3.HCl , which then forms an insoluble hydrogen bond network with HPO 4 2− (Scheme 8) [102].…”
Section: Sensing Of Phosphorus-containing Anionsmentioning
confidence: 99%
“…More recently, Zheng et al reported selective fluorescence turn-on sensing of PO 4 3− in water by TPE-derivative D3 [102]. The emission response is due to the fact that PO 4 3− abstracts a proton from D3.2HCl to form D3.HCl , which then forms an insoluble hydrogen bond network with HPO 4 2− (Scheme 8) [102]. This sensing process is highly reversible, with the addition of HCl resulting in the regeneration of D3 .…”
Section: Sensing Of Phosphorus-containing Anionsmentioning
confidence: 99%
See 1 more Smart Citation
“…TPE derivatives have also received significant interest in the development of supramolecular sensors which couple a luminescent response with molecular recognition events [14–18] . However, the considered employment of TPE‐derivatives within supramolecular host systems remains scarce, [19–22] with the overwhelming majority of reported examples reliant on irreversible chemical modification of the AIEgen core to sense the guest species [23] …”
Section: Introductionmentioning
confidence: 99%